The Impact of Coping Skills in Post-traumatic Growth of Healthcare Providers: When Mental Health Is Deteriorating Due to COVID-19 Pandemic - Prekazi, Lulejete; Hajrullahu, Vjosa; Bahtiri, Shegë; Kryeziu, Blerta; Hyseni, Blertë; Taganoviq, Besarta; Gallopeni, Florim (Frontiers in Psychology, 2021)
Background: Frontline healthcare providers are consistently exposed to potentially traumatic events while assisting patients with Covid-19 Kalaitzaki, Tamiolaki & Rovithis, 2020; Wu et al, 2019. Post-traumatic growth (PTG) happens when a person can transform trauma and use adversity in one’s advantage. In response to limited studies on positive outcomes that may occur from the pandemic; this study aimed to elucidate the positive impact of coping with COVID-19 outbreak on mental health, such as PTG. Methodology: The study comprised a sample of 691 healthcare providers, including physicians and nurses working in public health facilities in Kosovo, who were asked to complete a questionnaire with four parts: Socio-demographic, GHQ - 28, COPE and PTGI. A deterioration of mental health with somatic symptoms leading to the escalation due to Covid-19 outbreak was found. Results: Female healthcare providers reported more clinical symptoms as well as higher coping skills scores than men. The domains in which positive changes were most frequently observed were Relating to Others, New Possibilities and Personal Strength. The mediation analysis showed a significant indirect effect of coping skills on the relationship between mental health and PTG. Conclusion: The results suggest that levels of mental health exacerbation do not play a conclusive role in determining levels of PTG, as long coping mechanisms are in place. The development and implementation of interventions to minimize Covid-19-related mental health consequences, by fostering PTG among healthcare providers could be highly beneficial in pandemic response work.